Influence of SPS Decomposition Product 1, 3-Propane Disulfonic Acid on Electrolytic Copper Via Filling Performance. Issue 12 (1st January 2015) - Kimizuka, Ryoichi; Toda, Hisayuki; Eda, Tetsuro; Kishimoto, Kazuki; Oh, Reisei; Honma, Hideo; Takai, Osamu
Abstract : Formation of interlayer connections in semiconductor and printed circuit board packaging can be accomplished by filling vias using three additive component electrolytic copper deposition. One of the essential additives that enables filling performance, bis-(3-sulfopropyl) disulfide (SPS) oxidized during electrolysis to give 1, 3-propane disulfonic acid (PDS). In order to further elucidate the plating chemistry and improve performance, the electrochemical effects and the effects of PDS content in the electrolyte on resulting copper deposits were investigated. The crystallite structure and crystal structure transitions were investigated using X-ray diffractometry and the influence on physical properties of the deposit by internal strain analysis and extensibility. Combustion-infrared absorption spectrometry was used to determine the C and S content in the respective deposits. In all examinations, PDS content in the electrolyte was found to influence plating performance and deposit characteristics. The results suggested that PDS masked SPS and that co-deposition of PDS affected the deposit physical properties.